Micro-particle entrapment dynamics in microfluidic pulmonary capillary networks. (May 2022) - Belenkovich, Merav; Sznitman, Josué; Korin, Netanel
Abstract: The journey of vascular targeted carriers (VTC) in the circulatory system is highly intricate and includes navigation through different vessel structures, such as the vast pulmonary capillary network (PCN) in the lungs where particles can get entrapped and lead to blockage. Here, we leverage microfluidic PCN models to explore, for the first time, micro-particle capillary entrapment, in a well-controlled biophysical environment mimicking human physiological hemodynamics at true scale. This in vitro strategy mimics the challenges of vascular carrier transport during their journey in the smallest capillaries of the body (∼5 µm). Specifically, we explore in the PCN model entrapment dynamics of spherical micro-particles of different diameters (i.e. 3, 4 and 4.5 µm) at different concentrations, comparing their motion in cell-free buffer to that in the presence of red blood cells (RBCs). Notably, while 3 µm particles exhibit undisturbed transport in all of the examined concentrations, both in cell-free buffer and in the presence of RBCs, particles of 4 and 4.5 µm exhibit a concentration-dependent transport where the presence of RBCs leads in fact to reduced entrapment. Our experiments suggest that collisions of micro-particles with RBCs can facilitate their navigability, allowing for carrier transport that would lead otherwise to rapid entrapment in a cell-free environment. Altogether, the proposed preclinical in vitro assays offer rapid screening opportunities for design optimization of VTC transport in capillary networks.